Current cathode spots in the glow discharge normal regime as a stationary dissipative structure: macroscopic parameters - Ponomaryov, O.P.; Anisimov, I.O. (Вопросы атомной науки и техники, 2011)
Effect of the normal current density in the dc glow discharge normal regime is studied using a phenomenological model of stationary dissipative structures caused by the distributed feedback. The cathode layer is described as a bistable medium, governed by the Fisher-type reaction-diffusion equation for ions' density. Stability of normal cathode current structure and existence of the current-voltage characteristic section with the current independent voltage drop is explained using the proposed analogy. The main parameters of the dissipative structure such as travelling wave velocity and critical current of abnormal regime transition are calculated. Obtained results are in good correspondence with the parameters obtained from the numerical simulation of dc glow discharge.